Study of Breast Lesions in a Tertiary Care Centre : A Retrospective Study - Chaurasiya, Anand Kumar; Patel, Amit Kumar; Khatun, Tarannum; Jana, Debnarayan; Sarraf, Pramod Kumar (Med Phoenix, 2017)
Background: To study the prevalence of various type of breast lesions in a tertiary care centre. Methods : The period of study was one year , from 1st January 2015 to 31st December 2015. Patients with breast lesions who came to department of pathology for Fine needle aspiration cytology were included in the study. There were 55 patients who came to the department for Fine needle aspiration cytology during one year period. Information pertaining to patients were taken from the medical record section and department of pathology of National medical college. Results: Out of 55 cases 17 patients (9.35%) were diagnosed with fibroadenosis, which was the highest followed by fibroadenoma (12 cases- 6.6%). Ductal hyperplasia was the least diagnosed disorder which was seen in only one patient (0.5%). Carcinoma of breast was diagnosed in three patients (1.65%). There were three (1.65%) male patients with breast lesions who were diagnosed with gynaecomastia. Conclusion: This study revealed that fibroadenosis was the most common disorder among the patients who came for fine needle aspiration cytology of the breast. Med Phoenix Vol.2(1) July 2017, 48-51